The neurodivergent playbook : how neurodivergent people can crack the code of living in a world not for us - Zakreski, Matthew (Gifted Unlimited, 2024)
"In The Neurodiversity Playbook, Matthew "Dr. Matt" Zakreski, Psy.D., a clinical psychologist, condenses a decade of research on social-emotional functioning within the neurodivergent community into an accessible, practical guide for navigating the world. Dr. Zakreski offers insights into the challenges faced by neurodivergent individuals, focusing on aspects like making friends, maintaining relationships, emotional regulation, effective communication, and understanding social contexts. Each section presents case examples, clinical advice, and practical skills for social-emotional learning (SEL), applicable across school, home, work, and community settings. Distilling Dr. Matt's best therapy practices and most popular professional speeches, this book offers effective strategies to guide neurodivergent individuals in navigating their world"--